Monitoramento ambiental e análise dos fluxos de energia em florestas de várzea e terra firme da Amazônia Central - Silva, Larissa Passos da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
Energy flows and major climatic and environmental elements were evaluated at two sites located in the central Amazon, one of mainland (terra firme), in the Cuieiras’ Biological Reserve - ZF2, and other of low floodplain forest (várzea baixa) in the Mamirauá’s Sustainable Development Reserve (MSDR), in 2009-2010. Data were collected through a micrometeorological tower of 54 m in a plateau area in the mainland site (ML) and by means of a structure installed in a 20 m tree representative at the low floodplain site (LF). Methodologies that integrate information from composition and biomass forest were employed and data air relative humidity and temperature, soil heat flux and net radiation, and trunk temperatures were used to obtain the energy flows in the forests. According to the results the temperature and relative humidity showed mild seasonality. In ML, the average monthly cumulative rainfall was 46.2 % higher in the wet season (WS), compared to the dry season (DS), and in the LF this variable was only 16 % higher in the terrestrial period (TP, without water column presence) than in the flooded period (FP), while between WS and TP the variation was 38 %. In LF the annual fluctuation of the water level followed approximately the cycle of precipitation. In ML, the incident solar radiation (Rin) accumulated daily was higher in DS and lowest in the WS, and in LF this greatness showed weak variation between TP and FP. Between WS and TP, Rin was higher in WS. It was found that the layers where it was held the inter-sites comparative energy balance, the largest vertical temperature variation occurred in LF. Trunk temperatures in LF followed the air temperature, except at the level of 1.0 m, in the days of flooding. On selected days (preferably without precipitation), the net radiation (Rn) in ML was influenced by cloudiness, being higher in DS than in the WS, while in LF seasonality of this term was negligible. Probably motivated by lower amount of biomass, have been observed largest amounts of Rn in LF than in ML. The latent heat flux (LE) and sensible heat flux (H) followed approximately the behavior of the daily profile of Rn, but in ML, LE decreased 4.5 % and H increased 136 % between DS and WS, and in LF, H was about three times larger and LE 40 % lower in IP compared to TP. There were very small differences between WS and EN with respect to LE and H. It was found the energy storage (S) daily positive balance in ML, and in LF, in the IP, about 70 % of S was used in water (Ság), with a stock daily energy 93 % higher than in TP. We observed significant increase in energy storage in the air (Sar) in the WS, comparing it to the TP. At the end of day in ML, the heat flux in the soil (G) balance was positive in DS and negative in WS, and in LF there was a considerable influence of the water layer on this term in the IP, besides the difference in G between WS and EN was well marked. The woods used most daily Rn for LE (78.5 % on average in ML and 66.7% in LF) and about 19.1 % and 30.5 % of Rn at ML and LF, respectively, were employed in H. On average about 3 % of Rn was directed to S and G in the forests.
Keywords: Micrometeorologia; Clima; Razão de Bowen